A Novel Antenna Array Geometry for DOA Estimation - Sanjeev Kumar Dhull, Vinod Kumar (International Journal of Advanced Science and Technology, 2020)
The performance of array based direction finding system highly depends on array geometry, numbers of snapshot (array elements) and spacing between the elements. The non-uniform array gives better accuracy and resolution than uniform linear array. The main objective of the paper is to minimize the error of signal estimation array using Genetic Algorithm in which a novel non uniform circular array has been proposed in order to detect the signal directions. The performance of proposed array has been done on the basis of mean square error (MSE). The results obtained from performance comparison shows that the purposed array is better than the others in terms of estimation time and accuracy.